Supporting physiological birth choices in midwifery practice : the role of workplace culture, politics, and ethics. - Feeley, Claire (Abingdon, Oxon ; New York, NY : Routledge, 2023)
Highlighting the experiences of midwives who provide care to women opting outside of guidelines in the pursuit of physiological birth, Claire Feeley looks at the impact on midwives themselves, and explores how teams and organisations support or discourage women's birth choices. This book investigates the processes, experiences and sociocultural-political influences upon midwives who support women's alternative birthing choice and argues for a shift in perspective from notions of an individual's professional responsibility to deliver woman-centred care, to a broader, collective responsibility. The book begins by contextualising the importance of quality midwifery care with an exploration of the current debates to demonstrate how hegemonic birth discourse and maternity practices have detrimentally affected physiological birth rates, and the wellbeing of women who opt outside of maternity guidelines. It provides real life examples of how midwives can facilitate a range of birthing decisions within mainstream midwifery services. Moreover, an exploration of midwives' experiences of delivering such care is presented, revealing deeply polarised accounts from moral injury to job fulfilment. The polarised accounts are then presented within a new model to explore how a midwife's socio-political working context can significantly mediate or exacerbate the vulnerability, conflict and stigmatisation that they may experience as a result of supporting alternative birth choices. Finally, this book explores the implications of the findings, looking at how team and organisational culture can be developed to better support women and midwives, making recommendations for a systems approach to improving maternity services. Discussing the invisible nature of midwifery work, what it means to deliver woman-centred care, and the challenges and benefits of doing so, this is a thought-provoking read for all midwives and future midwives. It is also an important contribution to interprofessional concerns around workforce development, sustainability, moral distress and compassion in health and social care.
Keywords: Childbirth -- Social aspects; Childbirth -- Political aspects; Midwifery -- Decision making; Midwifery -- Practice; MEDICAL / Nursing / Maternity, Perinatal, Women's Health